Arquitetura japonesa entre tradição e contemporaneidade: o escritório Sanaa (1987-2015) - Rebellato, Livia (2021)
The present study aims to study the design methods of the japanese office SANAA, led by the architect Kazuyo Sejima and ger partners Ryue Nishizawa, located in the city of Tokyo, Japan. The path and genealogy of traditional japanese architecture in that it objectively and subjective subsidizes some possible concepts that have been applie in the design lines of this office that is currently recognized and internationally renowed for its work. The study seeks to understand there confluences and divergences present at the heart of the projects developed by SANAA, combining the japanese westernization that has been taking place since the end of the 19th century, modifying its traditional architecture with the introduction of new technologies and mechanisms of cultural exchanges the are mutual, for the contribution of modern and contemporary japanese architecture to the international environment.